T Transformasi Pendidikan Karakter dan Akhlak: Peran Pendidikan Islam dalam Era Industri (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
The industrial era brought profound transformations in the social, economic, and educational order, while presenting serious challenges to the formation of character and morals. The dominance of the logic of efficiency, instantaneousness, and individualism has the potential to erode the foundations of moral values that are transcendent and require a long-term internalization process. This research aims to analyze the impact of changes in industrial civilization on the construction of moral values, identify the basic principles of Islamic education in character formation, and explore its role as a mechanism of social transformation in the midst of secular paradigm hegemony. Using the library research method, this study analyzes primary sources of classical Islam—such as the thought of Ibn Miskawaih and al-Ghazali—as well as secondary sources in the form of scientific journals and contemporary studies. The findings show that Islamic education offers a holistic framework that places morality as the main axis of tarbiyah, not just a curricular complement. Principles such as tazkiyat al-nafs, uswah hasanah, and the integration of knowledge-charity-morals remain relevant when reinterpreted contextually in the digital ecosystem. More than that, Islamic education has the potential to be a balancing force that reconstructs the relationship between technology, ethics, and social responsibility, thus ensuring that the progress of civilization remains on the side of a whole humanity